GENDER-BASED DIFFERENCES IN COMPLIMENTS AND RESPECTIVE RESPONSES BETWEEN TEACHERS AND STUDENTS AT ILP KEDIRI - PRATIWI, DIAN (Jurnal Ilmiah Mahasiswa FIB, 2013)
Compliments are rarely uttered, and Indonesians tend to reject them. Moreover, there are not many studies investigating interlanguage compliments and compliment responses made by learners of English as a second or foreign language (Ernawati, 2004). As compliments are influenced greatly by the gender (Holmes, 1988), the writer conducted a study about compliments and compliment responses performed by teachers and students who are learners of English as a foreign language at ILP Kediri. There are two problems to be solved the study, namely; (1) How do compliments performed by female teachers differ from those performed by male ones? (2) How do compliment responses performed by female students differ from those performed by male ones?This study is categorized as a case study using qualitative approach since it was made of a group of individuals consisting of ILP Kediri teachers and students. To gather the data, the writer observes class activities at ILP Kediri.This study reveals that gender does not always influence the female and male teachers of ILP Kediri in giving compliments to their students and the female and male students in responding them. They share more similarities than differences. The teachers utter a word (Adjective), a noun phrase, or a simple sentence to compliment their students. A compliment in the form of a word is uttered the most by them. Regarding topics of compliments, the female teacher produces compliments on performance/ skill/ ability and on personality whereas the male one produces compliments on performance/ skill/ ability and on appearance. Yet, a compliment on performance/ skill/ ability is performed the most by two of them. Next, the female and male students either disagree or agree with compliments they got. They disagree with a compliment on performance/ skill/ ability by giving no response and agree with a compliment on personality by using a non-verbal acceptance. The differences occur when the male students also disagree with a compliment on performance/ skill/ ability by claiming that the compliment is overstated and showing flaw and agree with it by using non-verbal acceptance and when the female students agreed with a compliment on performance/ skill/ ability by mentioning her friends to transfer the complimentary force and using verbal acceptance and agree with a compliment on appearance by using non-verbal acceptance.The writer suggests ILP Kediri’s teacher keep complimenting their students in order to encourage them in studying and the future researchers conduct studies by obtaining data from different contexts and situations or investigating differences in compliments and compliment responses based on genders with different ages, relationships, or status. Keywords: speech acts, gender, compliments, compliment responses